Electricity consumption optimization of power users driven by a dynamic electric carbon factor - Yang, Yuyao; Pan, Feng; Li, Jinli; Ji, Yilin; Zhong, Lihua; Zhang, Jun (Frontiers in Energy Research, 2024)
In light of the escalating concerns surrounding climate change and air quality degradation, the imperative for energy conservation and emission reduction has garnered widespread attention. Given that factories represent a significant portion of electricity consumption within the power network, a comprehensive analysis of the electricity consumption behaviour of energy-intensive enterprises becomes paramount. To meticulously dissect the electricity consumption patterns of energy-intensive enterprises, this paper categorizes them into four distinct production modes: 24-Hour All-day Production Factories, Pure Daytime Production Factories, Pure Night-time Production Factories, and Environmentally Friendly Peaking Production Factories. Employing the dynamic electricity-carbon factor as a guiding force, the analysis encompasses electricity consumption, tariff expenditure, peaking costs, carbon emissions, and comfort levels associated with each production method throughout the year. A delicate equilibrium is sought among multiple objectives, aiming to optimize user experience while simultaneously mitigating costs and carbon emissions. Furthermore, this paper conducts a comparative analysis of each objective, employing single-objective genetic algorithms and the interior point method. The resultant findings serve as invaluable insights for business users, aiding in informed decision-making processes.